Bats (Chiroptera) in the collection of the Zoological Museum of Lviv University, Ukraine - Shydlovskyy, I.; Zatushevsky, A.; Kusnezh, O. (Theriologia Ukrainica, 2018)
The theriological collection of the Zoological Museum of Ivan Franko National University of Lviv was amassed during 142 years. It has over 3,800 exhibits, among which 343 (9 %) are bats (Chiroptera) that belong to 32 species. The bat collection is represented by study skins (254 exhibits) which are being preserved in 22 special boxes. Stuffed and almost all fluid-preserved specimens of bats are presented only in the exposition. Besides, there are 6 skeletons and 11 skulls in the collection, which belong to at least 9 species of bats. The main part of the collection was gathered in Western Ukraine, and only a few samples originate from the South and East of Ukraine. In particular, the type series of Khazarian serotine Eptesicus lobatus Zagorodniuk, 2009 was brought from Eastern Ukraine. Tropical species are also presented in the collection: Hipposideros caffer, Epomophorus labiatus, Pteropus vampyrus, and species of the genera Neoromicia and Rousettus. The bat collection was amassed during 1900–2015. It widely represents the bat fauna of the Carpathian region and Transcarpathian lowland. Теріологічна колекція Зоологічного музею ЛНУ ім. І. Франка зібрана упродовж 142 років та налічує понад 3 800 музейних зразків, з яких 343 зразки, або 9 % — рукокрилі (Chiroptera) 32 видів. За типами музейних зразків колекція представлена тушками (254 екз.), які зберігаються у 22 спеціальних коробках. Опудала та майже всі мокрі препарати кажанів представлені в експозиції. Крім того, у колекції зберігаються шість скелетів та 19 черепів, що належать не менше ніж 9 видам кажанів. Основна частина колекції зібрана в межах західних областей України і лише поодинокими зразками представлено південь та схід. Зі cходу України, зокрема, є типовий матеріал пергача донецького, Eptesicus lobatus Zagorodniuk, 2009. Тропічні види представлені у колекції видами Hipposideros caffer, Epomophorus labiatus, Pteropus vampyrus, представниками родів Neoromicia та Rousettus. Хронологічно колекція зібрана упродовж 1900–2015 рр. Вона широко репрезентує хіроптерофауну регіону Карпат та Закарпатської низовини.